The Kodály Method and Tonal Harmony: An Issue of Post-secondary Pedagogical Compatibility - Penny, Lori Lynn (Université d'Ottawa / University of Ottawa, 2012)
This study explores the topic of music theory pedagogy in conjunction with the Kodály concept of music education and its North-American adaptation by Lois Choksy. It investigates the compatibility of the Kodály Method with post-secondary instruction in tonal harmony, using a theoretical framework derived from Kodály’s methodology and implemented as a teaching strategy for the dominant-seventh chord. The customary presentation of this concept is authenticated with an empirical case study involving four university professors. Subsequently, Kodály’s four-step instructional process informs a comparative analysis of five university-level textbooks that evaluates the sequential placement of V7, examines the procedure by which it is presented, and considers the inclusion of correlated musical excerpts. Although divergent from traditional approaches to tonal harmony, Kodály’s principles and practices are pedagogically effective. By progressing from concrete to abstract, preceding symbolization with extensive musical experience, conceptual understandings are not only intellectualized, but are developed and internalized.
Keywords: music theory pedagogy; the Kodály Method; Zoltán Kodály; Lois Choksy; Edward Aldwell; Carl Schachter; Harmony and Voice Leading (2003); Jane Piper Clendinning; Elizabeth West Marvin; The Musician’s Guide to Theory and Analysis (2005); Robert Gauldin; Harmonic Practice in Tonal Music (2004); Stefan Kostka; Dorothy Payne; Tonal Harmony (2004); Miguel Roig-Francolí; Harmony in Context (2003)